Mechanical, electrical and electro-mechanical properties of thermoplastic elastomer styrene–butadiene–styrene/multiwall carbon nanotubes composites - Costa, P. (2013)
Composites of styrene–butadiene–styrene (SBS) block copolymer with multiwall carbon nanotubes were processed by solution casting to investigate the influence of filler content, the different ratios of styrene/butadiene in the copolymer and the architecture of the SBS matrix on the electrical, mechanical and electro-mechanical properties of the composites. It was found that filler content and elastomer matrix architecture influence the percolation threshold and consequently the overall composite electrical conductivity. The mechanical properties are mainly affected by the styrene and filler content. Hopping between nearest fillers is proposed as the main mechanism for the composite conduction. The variation of the electrical resistivity is linear with the deformation. This fact, together with the gauge factor values in the range of 2–18, results in appropriate composites to be used as (large) deformation sensors.